2008
DOI: 10.1016/j.pep.2007.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Soluble expression and purification of the oxidoreductase component of toluene 4-monooxygenase

Abstract: Toluene 4-monooxygenase (T4MO) is a member of the bacterial multicomponent monooxygenases, an enzyme family that utilizes a soluble diiron hydroxylase to oxidize a variety of hydrocarbons as the initial step in their metabolism. The hydroxylases obtain reducing equivalents from NAD(P)H via an electron transfer chain that is initiated by an oxidoreductase containing an N-terminal ferredoxin domain and C-terminal flavin-and NAD-binding domains. T4moF, the NADH oxidoreductase of T4MO, was expressed as a soluble p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…4). It was reported that the reductase components of binuclear iron monooxygenases that contain [Fe-S] centers were amenable to inactivation in E. coli cells, particularly under high-level-expression conditions (15,24,32). For example, the reductase component of toluene 4-monooxygenase has been functionally expressed under the control of a weak promoter (32).…”
Section: Discussionmentioning
confidence: 99%
“…4). It was reported that the reductase components of binuclear iron monooxygenases that contain [Fe-S] centers were amenable to inactivation in E. coli cells, particularly under high-level-expression conditions (15,24,32). For example, the reductase component of toluene 4-monooxygenase has been functionally expressed under the control of a weak promoter (32).…”
Section: Discussionmentioning
confidence: 99%
“…T4moF cell paste was re-suspended in 25 mM MOPS, pH 7.5, containing 80 mM NaCl and 2% glycerol at a ratio of 1.5 ml per g of wet cell paste 55 . The cell-free extract was prepared as described above for T4moH.…”
Section: Methodsmentioning
confidence: 99%
“…The cofactor flavin in holo‐CpmtFNR was further detected and confirmed by an isocratic chromatography‐based method. Greater than 50% of the recombinant CpmtFNR protein contained the cofactor FAD as determined by comparing the sample peak intensity to a standard curve prepared from authentic FAD as previously reported 34…”
Section: Resultsmentioning
confidence: 99%
“…For the expression of the CpmtFNR protein, a modified terrific broth containing 20 m M glucose, 2 g/L NaNO 3 , and 50 μg/mL ampicillin was used. After growing bacteria at 37°C until OD 600 reached 0.5–0.6, riboflavin (0.01 m M ) and isopropyl‐β‐D‐thio‐galactoside (IPTG) (0.1 m M ) were added into the medium as previously reported 34. The subsequent overexpression was allowed to continue overnight at 16°C.…”
Section: Methodsmentioning
confidence: 99%